Rôle De La Fracturation Dans La Circulation Des Eaux Souterraines Et La Répartition Des Sources : Cas Du Bassin Hydrogéologique De Sefrou (Moyen Atlas Septentrional, Maroc) - Idrissi, Bouhsine El Fellah; Hinaje, Said; Cherai, Bouamama; Mehdi, Khalid (European Scientific Journal, ESJ, 2016)
The formation of the basin of Sefrou is related to the normal successive movements of the faults N130, N80, N30 and N170 which follow one another since the upper Miocene until the recent medium-Quaternary. Seeing the dynamic of groundwater in the carbonated lands (Liasic dolomites) is primarily guided by the fractures and the cracks; we propose to study the influence of brittle tectonics on the spatial organization of the flows and the relation of the groundwater circulation with the fracturing. The analysis of the fracturing (affecting the Flavio-lake and travertines deposits of plio-quaternary age and their Miocene and Jurassic substratum) and the structural cuts as well as the correlation of the piezometric map established from the piezometric reports with that of the fracturing, allowed us to note that the fractures play a very important part in the geometry of the Liasic aquifer and the mode of the circulation of groundwater. This circulation is dependent on the zones of weaknesses along the faults and fractures. Water emergences are very variable and controlled by the paramount influence of the nature of the lithological formations and the tectonic structure on underground circulations. Indeed, the sources of water located in the basin of Sefrou are indexed, according to their origin, inside two types: sources of emergence and sources of discharge.